Degrees of jurisdiction and the notion of appeal in the Neo-Assyrian period - Villard, Pierre (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
The theme of the king of justice (šar kitti u mīšari) is recurrent in ancient Mesopotamia, where a ruler presented himself as the ultimate source of law, as the guarantor of a form of social justice aimed at repairing the effects of crises, and as the arbiter ensuring that everyone was entitled to equitable decisions of justice. This is illustrated, for example, by these formulas taken from the epilogue of the Code of Hammu-rabi: «so that the mighty do not oppress the weak, to provide justice to the orphan (and) to the widow» or «let any wronged man who is involved in a case come before my statue of the ‘King of Justice’ and have my inscribed stela read aloud to him, thus may he hear my precious decrees.» Despite the affirmation of these principles, the weakest often had difficulty asserting their rights. In practice, at the local level, the stronger party often had the means to impose his point of view before a court of law or to refuse to apply a decision that was unfavourable to him. It is true that the concept of the «king of justice» implied that one could appeal to the supreme authority, i.e. the sovereign himself, if one felt aggrieved. The letters of petition that have been found show that this was not just a theoretical possibility. It remains to be seen, however, how the king acted in matters of justice.